Quality Cost Analysis in the Assessment of the Effectiveness of the Quality Management System - Patrycja KOKOT-STĘPIEŃ (Communications of International Proceedings, 2021)
Quality costs are a measure of the effectiveness of activities related to the quality management system functioning in the enterprise. They constitute an instrument supporting decision-making, which should lead to the reduction of the company's own costs. However, in order for them to fulfill this role, it is necessary to know the amount of costs incurred on quality and the relations between them. The determination of quality costs and their control in order to optimize them enables the quality cost accounting, which is an important tool for identifying areas of efficiency improvement. The article analyzes the costs of quality in a steel industry company and, on the basis of cost indicators, the effectiveness of the quality management system functioning in the unit was assessed.
Keywords: Quality cost; Quality Management System